Pengaruh Gaya Hidup Dan Motivasi Belanja Terhadap Keputusan Pembelian Produk Fashion Di Matahari Departement Store Metropolitan Mall BekasiAbstract. This research was motivated by the increasing number of visitors to Matahari Department Store Metropolitan - Dian Yunita Lestari; Trie Andari Ratna Widyastuti (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This research was motivated by the increasing number of visitors to Matahari Department StoreMetropolitan Mall Bekasi after the Covid-19 pandemic. The research objects that are the independentvariables are lifestyle (X1) and shopping motivation (X2), while the buyer's decision (Y) is the relatedvariable. sampling in this study used the probability sampling method (random sampling) of 100respondents who visited Matahari Department Store Metropolitan Mall Bekasi. The analysis techniqueused was multiple linear regression analysis. The results of the simultaneous hypothesis test, lifestyle(X1) and shopping motivation (X2) together have a significant positive effect on purchasing decisions(Y). Based on the results of the coefficient of determination test, is 85%, the rest is influenced by otherfactors not included in this study.Keywords: Lifestyle, Shopping Motivation, Purchasing Decision